Effect of melatonin on epididymal sperm quality after testicular ischemia/reperfusion in rats - Kurcer, Zehra; Hekimoglu, Askin; Aral, Faruk; Baba, Fusun; Sahna, Engin (Elsevier Science Inc, 2010)
Objective: To determine the effect of melatonin, a pineal secretory product that prevents testicular ischemia/reperfusion (IR) injury through its antioxidative properties, on epididymal sperm quality in a rat testicular IR injury model. Design: Experimental study. Setting: University pharmacology laboratory. Animal(s): Fifty-six 8-week-old male Wistar albino rats. Intervention(s): Left testicular artery and vein occluded for I hour; before the bilateral orchiectomy, the organ was allowed to reperfuse 30 days. Melatonin (10 mg/kg IP) or vehicle (1% ethanol in saline) was administrated for 10 minutes before reperfusion and for 1 hour after reperfusion. Main Outcome Measure(s): After 24 hours of reperfusion, the rats were decapitated, and the testicular tissue samples were obtained for histologic examination. In addition, after 30 days of reperfusion, the epididymal sperm concentration, motility, and abnormal sperm rates were determined in the sperm collected from the epididymis. Result(s): A statistically significant decrease in sperm concentration resulted from IR as well as an increase in sperm abnormalities, but the sperm motility did not change. Melatonin treatment did not prevent the IR-induced reduction in sperm concentration. However, melatonin treatment statistically significantly decreased the sperm abnormalities when compared with the IR injured samples. Conclusion(s): Melatonin may improve sperm morphology for a protective effect in IR-induced testicular injury. (Fertil Steril (R) 2010;93:1545-9. (C)2010 by American Society for Reproductive Medicine.)
Keywords: Melatonin; testicular ischemia/reperfusion; sperm concentration; sperm motility; sperm morphology